2015
DOI: 10.1038/gt.2014.120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo antitumor effects of ANT2 shRNA delivered using PEI and ultrasound with microbubbles

Abstract: Gene therapy using RNA interference can be directed against tumors through various strategies, but has been hindered owing to the inefficiency of non-viral delivery. To evaluate the antitumor effects of adenine nucleotide translocase-2 (ANT2) short hairpin RNA (shRNA) by intraperitoneal injection using the polyethylenimine (PEI) and an ultrasound gene delivery method, human breast carcinoma MDA-MB-231 cells were injected subcutaneously into NOG (NOD/Shi-scid/IL-2Rγ(null)) mice. The results showed greater tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Despite a high number of publications demonstrating the ability of FUS to deliver gene bearing liposomes[152,153], non-viral polyplexes[154156], viruses[157159] and free or MB bound plasmid DNA[160] to non-CNS tissues, there are very few studies that have shown the delivery of systemically administered gene-bearing agents to the CNS with FUS. Indeed, the first successful studies showing delivery of reporter gene-bearing agents across the BBB with FUS were completed as recently at 2012[161163].…”
Section: Gene Deliverymentioning
confidence: 99%
“…Despite a high number of publications demonstrating the ability of FUS to deliver gene bearing liposomes[152,153], non-viral polyplexes[154156], viruses[157159] and free or MB bound plasmid DNA[160] to non-CNS tissues, there are very few studies that have shown the delivery of systemically administered gene-bearing agents to the CNS with FUS. Indeed, the first successful studies showing delivery of reporter gene-bearing agents across the BBB with FUS were completed as recently at 2012[161163].…”
Section: Gene Deliverymentioning
confidence: 99%
“…Furthermore, one of the major concerns associated the use of these enhancers in clinical studies is the safety of the therapeutic system ( 38 ). Non-viral vectors are being increasingly used for gene therapy instead of viral vectors, owing to the concerns about the potential induction of immune responses against viral proteins, endogenous virus recombination and oncogenic effects ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, it was identified that the UTMD delivery method exhibited potential in improving gene transfection efficiency. The toxicity of the nanobubbles and the ultrasound radiation have also raised crucial safety issues in clinical studies ( 38 ). Therefore, liver and kidney samples were collected from each group of nude mice, and H&E staining was performed to evaluate the safety of the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deshpande et al found that ultrasound combined with PEI could enhance the DNA transfection rate up to 200-fold than naked DNA plasmids [59]. Park et al applied UTMD combined with PEI mediating the adenine nucleotide translocase-2 (ANT2) shRNA to successfully increase the survival rate of xenograft mice and induce the tumor regression [60].…”
Section: Nanoparticle Nanodroplet and Nanobubblementioning
confidence: 99%